Representation of Minangkabau Cultural Values in Minangkabau Tiger Martial Art on Instagram: A Semiotic Study Based on Charles Sanders Peirce’s Theory - Muntriani, Ifdhollia; Widaningsih, Themotia Titi (The Eastasouth Journal of Social Science and Humanities, 2025)
This study aims to analyze how Minangkabau cultural values are represented through the Minangkabau Tiger Silat account on Instagram. Using a qualitative approach and Charles Sanders Peirce’s semiotic theory, this research investigates how signs in the form of icons, indexes, and symbols are used to depict cultural meanings. The data were collected through observation, documentation, and interviews with silat practitioners. The results show that Instagram visuals can successfully present philosophical values such as religiosity, reverence for ancestors, harmony with nature, and resilience. This study contributes to the growing field of cultural communication in digital media and suggests future studies to explore audience engagement in cultural preservation efforts online.